A comparative legal analysis of the rights granted to muslim illegitimate children under syariah law and civil law / Nur Shahidhzul Naqieya Zulkernain and Nurul Azmelia Abu Bakar - Zulkernain, Nur Shahidhzul Naqieya; Abu Bakar, Nurul Azmelia (2010)
This research is an attempt to critically determine the legal status and the rights of the illegitimate child as well as the rights bestowed on the parents. A child would be regarded as an illegitimate child if he was born as a consequence of unlawful sexual intercourse. A child who was born before six months of the lawful marriage can be considered as an illegitimate child. The presumption of legitimacy of a child can be rebutted as it has been stipulated under Islamic law and Civil law. It should be noted that, once the child has been regarded as an illegitimate child, his rights would be different to the rights granted to a legitimate child. The illegitimate child would only be deemed to be the child of the mother. The relationship between the mother and the child would always be recognized, as provided under Islamic law. Unfortunately, the paternity of the child cannot be established under Islamic law; therefore, the father has no rights over the said child. Due to this fact, this research examines the reasons the rights of the father cannot be recognized. Data and information of this research were gathered from various sources including textbooks, internet databases and interviews. Findings show that the illegitimate child cannot be discriminated and should be treated equally. Nonetheless, the law limits the rights of the illegitimate child in various circumstances. It is hoped that this research can be useful to illustrate the legal status of and the rights granted to illegitimate children.